Assessing the Impacts of IFRS Adoption in Emerging Economies : Evidence from Saudi Arabia - Chehade, Sarah; Procházka, David, 1979 říjen 10.-; Alsharairi, Malek; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2024)
In 2012, the road map for the transition to International Financial Reporting Standards (IFRS) entitled “SOCPA Project for the transition to International Accounting and Auditing Standards” was proposed by the Saudi Organization for Certified Public Accountants (SOCPA) alongside the Saudi Arabian Monetary Authority (SAMA) and the Capital Market Authority (CMA). Under this convergence plan, the effective adoption date of IFRS standards in Saudi Arabia was set to be January 1, 2017, requiring all listed companies to shift from local GAAP to IFRS. Multiple studies have investigated the implementation of IFRS in the case of developing countries covering the importance of this adoption, its benefits, challenges, and impacts (Barth et al., 2008; Cameran et al., 2014; Sellami & Fakhfakh, 2014; Capkun et al., 2016; Chen et al., 2010). However, less frequent researchers have investigated the IFRS transition and the associated consequences in the case of Saudi Arabia. This thesis fills in the gap of empirically assessing the impacts of IFRS adoption in the case of emerging economies and more precisely in the case of Saudi Arabia covering the impact on earnings’ quality, value relevance of accounting information, Foreign Direct Investments (FDI), and stock market development. This thesis focuses on the adoption of IFRS in the case of Saudi Arabia, one of the leading countries in the emerging MENA region, to assess whether these standards have been beneficial or detrimental. Multiple important factors led to this selection: Saudi Arabia is the largest economy in the Middle Eastern area and a permanent and founding member of OPEC (Organization of the Petroleum Exporting Countries) as well as a participant in the G20 forum and the World Trade Organization (WTO); Moreover, the economy of Saudi Arabia is transitioning to a contemporary market economy from an economic paradigm that is primarily dependent on oil exports.
Furthermore, the context of Saudi Arabia that is modeled by the Shariah law has accepted together with other regional particulars, the motivators, and the barriers of the adoption of IFRS. This thesis provides an extensive background on Saudi Arabia considering the country, its demographics, the impact of religion on accounting profession, and the economic development as well as the history of accounting regulation in the country. The quantitative approach adopted to investigate the microeconomic impacts of IFRS adoption includes two main streams, namely earnings’ quality and value relevance of accounting information. For this end, the sample included non-financial listed firms for the period between 2014 and 2019 covering the pre-and post-IFRS adoption years. The sample of earnings’ quality models included 87 firms and 522 firm-year observations; however, the sample for the value relevance of accounting information included 98 firms and 588-firm years observations. To measure earnings’ quality, three hypotheses and in return three models were developed representing earnings smoothing, managing earnings toward a target, and timely loss recognition. However, for the value relevance of accounting information, two models were developed namely the Ohlson basic price model, and the expanded model. The results generated from the statistical analysis significantly confirm the positive impact of IFRS adoption on value relevance of accounting information and more precisely on the value relevance of equity, earnings, and cash flow from operations. Contrariwise, the results fail to provide supporting evidence concerning the positive impact of IFRS adoption on earning’s quality in Saudi Arabia. At the macroeconomic level, the impact of IFRS adoption on FDI and stock market development is assessed using a sample of four GCC countries namely: Kuwait, Qatar, UAE, and Saudi Arabia with a period standing between 1990 and 2020 for FDI and 2005 and 2021 for stock market
Vedoucí práce: David Procházka
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: accountancy and financial management [obor disert. práce]; disertace; dissertations